A Mobile Application for Calculating Nutrition of Cervical Cancer Patien - Younanda Mirah Fransisca; Adhisty, Karolin; Firnaliza Rizona (Caring: Indonesian Journal of Nursing Science, 2023)
Nutritional balance is one of the complex problems that can occur in cervical cancer patients. This problem can lead to a decrease in the quality of life of patients during treatment, so the nutritional needs of cervical cancer patients must be controlled and maintained in order to improve the quality of life of patients. It takes a nutrient that cervical cancer patients can use to help them calculate and balance these nutritional needs. This study aimed to create an application to help cervical cancer patients manage their nutritional needs. Research and development research was carried out using the ADDIE method. A limited test of this application was carried out by involving 30 cervical cancer patients who meet the inclusion criteria, namely, cervical cancer patients who had received curative treatment in the form of chemotherapy or radiotherapy in the Cancer Information and Support Center (CISC). The average score of the System Usability Scale used in this limited test was obtained with a value of 79.90 which was in the good and acceptable category. This application can certainly be one way to help cervical cancer patients in managing nutrition and improving their quality of life. Â